2016
DOI: 10.1016/j.ijdevneu.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of developmental alcohol and valproic acid exposure on play behavior of ferrets

Abstract: Exposure to alcohol and valproic acid (VPA) during pregnancy can lead to fetal alcohol spectrum disorders and fetal valproate syndrome, respectively. Altered social behavior is a hallmark of both these conditions and there is ample evidence showing that developmental exposure to alcohol and VPA affect social behavior in rodents. However, results from rodent models are somewhat difficult to translate to humans owing to the substantial differences in brain development, morphology, and connectivity. Since the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…an animal model of ASD [36,37,40,44,57]. However, VPA exposure during early postnatal life can also induce ASD -like behavioral phenotypes in mice [35,56] and ferrets [45]. These studies indicate that VPA exposure can induce an animal model of ASD over a wide range of exposure durations, from the second trimester to infancy.…”
Section: Plos Onementioning
confidence: 77%
See 3 more Smart Citations
“…an animal model of ASD [36,37,40,44,57]. However, VPA exposure during early postnatal life can also induce ASD -like behavioral phenotypes in mice [35,56] and ferrets [45]. These studies indicate that VPA exposure can induce an animal model of ASD over a wide range of exposure durations, from the second trimester to infancy.…”
Section: Plos Onementioning
confidence: 77%
“…Developmental VPA exposure can induce ASD-like behavioral phenotypes, including reduced social interaction in mice [35,56], rats [36][37][38], common marmosets [57], and ferrets [45]. VPA-induced behavioral deficits might be associated with cortical dysgenesis characterized by increasing neuron numbers and cortical thickening in humans [39], mice [41,43], and rats [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Valproic acid (VPA), a well-known antiepileptic/anticonvulsant drug, also acts as an inhibitor of histone deacetylases 1 and 2 ( Göttlicher et al, 2001 ; Phiel et al, 2001 ). Many studies have reported autism spectrum disorder (ASD)-like behavioral abnormalities induced by VPA exposure during prenatal and neonatal periods in various mammalian species such as mice ( Yochum et al, 2008 ; Burenkova et al, 2014 ), rats ( Miyazaki et al, 2005 ; Mychasiuk et al, 2012 ; Favre et al, 2013 ), common marmosets ( Yasue et al, 2018 ), and ferrets ( Krahe et al, 2016 ). These behavioral abnormalities are believed to be associated with cerebral cortical abnormalities caused by developmental VPA exposure ( Sabers et al, 2014 ; Wood et al, 2014 ; Fujimura et al, 2016 ; Lauber et al, 2016 ; Sawada et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%